Edward Thompson's Warrens: On the Transition to Socialism and Its Relation to Current Left Mobilizations - Lynd, Staughton (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2002)
Abstract Edward Thompson developed a distinct view of the transition from capitalism to socialism. Rejecting the concept of a catastrophic change in which the vanguard party would serve as the institutional nucleus of a new society, Thompson argued that capitalism had been “warrened” from within by a network of local, self-governing, working-class institutions that prefigured a socialist world. In the mid-1960s, however, Thompson turned to other matters and failed to resolve the longstanding debate on the Left about the role of trade unions in a transition to socialism. Recent events in Seattle, Qué bec City, and Genoa suggest that workers and students acting through new institutions improvised for the occasion must work together in actually bringing about revolutionary change. The same pattern shows itself in highpoints of working-class activity in the 20th century, as in Russia in 1905 or Hungary in 1956.